Synergistic effect of rice tungro virus and Sarocladium oryzae in relation to the incidence of sheath rot disease - K.N. BHAGABATI, B.D. SARMA and (Indian Phytopathology, 2002)
Pot-grown rice cv. Jaya plants were inoculated at different growth stages with rice tungro virus (RTV), Sarocladium oryzae (the causal agent of sheath rot) or a combination of both pathogens to study the effects of these pathogens on the incidence of sheath rot. In addition, changes in the carbohydrate level due to RTV infection and its effect on sheath rot incidence were studied. The results showed that sheath rot symptoms appeared much earlier in RTV-infected rice plants compared to the plants infected with S. oryzae alone. Also, sheath rot incidence was significantly higher in rice plants infected by RTV. Carbohydrate content was increased by RTV infection and a positive correlation (r = 0.99) was observed between sheath rot incidence and carbohydrate accumulation. Yield reduction was greatest when both pathogens were present, compared to each pathogen alone.